THE IMPORTANCE OF PHRASEOLOGICAL UNITS IN DESCRIBING “HUMAN CHARACTER” IN ENGLISH AND UZBEK FICTION - Shokirova Markhabo Sharifovna; Rakhimov Davron Mutalib o'gli (Western European Studies, 2024)
This article discusses the importance of phraseological units in describing "human character" in English and Uzbek fiction and the scientific-theoretical aspects of the semantic and linguocultural characteristics of phraseology in English and Uzbek languages
Keywords: phraseology; phrase; method; nation